P. SABANSKY'S CAMPAIGNS TO TELETSKOYE LAKE AND F. PUSHCHIN’S CAMPAIGNS TO THE BIYA RIVER: TIME, REASONS, CONSEQUENCES - V. N. Dobzhanskii (Вестник Кемеровского государственного университета, 2017)
The campaigns of Tomsk service people F. Pushchin and P. Sabansky to the river Biya and Teletskoe Lake are well known to Siberian historians. The historiography of these campaigns is poor and limited to the works of G. F. Miller, I. E. Fisher and A. P. Umansky. The source base these researchers relied on is poor as well. Until recently it was limited to the four documents of the "Tomsk archives", three of which were published by A. I. Andreev in the annex to the "History of Siberia" by G. F. Miller. Until recently the interpretation of these campaigns by I. Fisher and A. P. Umansky were beyond doubt. However, a comparative analysis of the documents, which the researchers used to describe the campaigns of F. Pushchin and P. Sabansky, showed their contradictions and incorrect dating, also the reasons for these campaigns were unknown. In the collection of the Siberian order of The Russian State Archives Ancient Acts we discovered a statement about the campaign of P. Sabansky on Teletskoe Lake which settles these differences and makes it possible to set the exact time, the causes and the sequence of the campaigns.